Effect of Pineapple Extract Concentration and Soaking Duration on Germination and Vigor of Seedless Watermelon (Citrullus lanatus L.) Seeds - Dwi Rahmawati; Zaki Afifah (International Journal of Technology, Food and Agriculture, 2026)
Seedless watermelon (Citrullus lanatus L.) seeds commonly exhibit physical dormancy due to a hard and impermeable seed coat that restricts water uptake and delays germination. Pineapple extract containing the proteolytic enzyme bromelain offers a natural alternative to mechanical cracking by facilitating seed coat softening. This study evaluated the effects of pineapple extract concentration and soaking duration on dormancy breaking and early seed performance of seedless watermelon. A factorial Completely Randomized Design was applied using three extract concentrations (25%, 50%, and 75%) and three soaking durations (5, 10, and 15 minutes). Germination percentage, radicle emergence, and vigor index were measured. The results showed that extract concentration and soaking duration significantly affected germination percentage and vigor index, while their interaction significantly influenced radicle emergence. The highest performance was consistently achieved at a 25% extract concentration with 5 minutes of soaking, resulting in 64.22% germination, 70.67% radicle emergence, and 53.56% vigor index. These findings indicate that moderate enzymatic treatment enhances dormancy breaking by promoting protein hydrolysis and improving early metabolic activation. The novelty of this study lies in identifying the optimal interaction between pineapple extract concentration and soaking duration for improving multiple physiological indicators of seed performance. Pineapple extract can therefore be considered a practical, natural, and environmentally friendly alternative for improving dormancy breaking and early seed performance in seedless watermelon.